Differential rescue of visceral and cardiac defects in Drosophila by vertebrate tinman-related genes. - Park, M.; Lewis, C.; Turbay, D.; Chung, A.; Chen, J.N.; Evans, S.; Breitbart, R.E.; Fishman, M.C.; Izumo, S.; Bodmer, R. (Proceedings of the National Academy of Sciences of the United States of America, 1998)
tinman, a mesodermal NK2-type homeobox gene, is absolutely required for the subdivision of the early Drosophila mesoderm and for the formation of the heart as well as the visceral muscle primordia. Several vertebrate relatives of tinman, many of which are predominately expressed in the very early cardiac progenitors (and pharyngeal endoderm), also seem to promote heart development. Here, we show that most of these vertebrate tinman-related genes can readily substitute for Drosophila tinman function in promoting visceral mesoderm-specific marker gene expression, but much less in promoting cardiac-specific gene expression indicative of heart development. In addition, another mesodermal NK2-type gene from Drosophila, bagpipe, which is normally only needed for visceral mesoderm but not heart development, cannot substitute for tinman at all. These data indicate that the functional equivalence of the tinman-related subclass of NK2-type genes (in activating markers of visceral mesoderm development in Drosophila) is specific to this subclass and distinct from other homeobox genes. Despite the apparent overall conservation of heart development between vertebrates and invertebrates, the differential rescue of visceral mesoderm versus heart development suggests that some of the molecular mechanisms of organ formation may have diverged during evolution.